2014
DOI: 10.1007/s10709-014-9791-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal evolution in the Drosophila cardini group (Diptera: Drosophilidae): photomaps and inversion analysis

Abstract: Detailed chromosome photomaps are the first step to develop further chromosomal analysis to study the evolution of the genetic architecture in any set of species, considering that chromosomal rearrangements, such as inversions, are common features of genome evolution. In this report, we analyzed inversion polymorphisms in 25 different populations belonging to six neotropical species in the cardini group: Drosophila cardini, D. cardinoides, D. neocardini, D. neomorpha, D. parthenogenetica and D. polymorpha. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…The two de novo assemblies had high BUSCO scores ( D. dunni scored 93.9%: 2627 complete, 79 fragmented and 93 missing out of 2799 total; D. nigrodunni scored 97.3%: 2721 complete, 37 fragmented and 41 missing out of 2799 total). Consistent with previous findings that failed to detect inversions within the dunni group ( Cordeiro et al 2014 ), we found no large structural rearrangements between genomes, and no evidence of fixed inversions between species in the dunni group ( Heed 1962 ; Cordeiro et al 2014 ), though we do find several inversions between the next closest whole genome available, D. innubila on Muller elements B, C and D ( D. nigrodunni shown in Supplementary Figure 4B). We annotated the dunni group genomes using a transcriptome from D. innubila in MAKER ( Holt and Yandell 2011 ) and found between 10752 and 11581 genes in the assembled genomes of each species, most of which show orthology to previously identified genes in D. virilis, D. melanogaster or D. innubila (Supplementary Table 5) ( Hill et al 2019 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The two de novo assemblies had high BUSCO scores ( D. dunni scored 93.9%: 2627 complete, 79 fragmented and 93 missing out of 2799 total; D. nigrodunni scored 97.3%: 2721 complete, 37 fragmented and 41 missing out of 2799 total). Consistent with previous findings that failed to detect inversions within the dunni group ( Cordeiro et al 2014 ), we found no large structural rearrangements between genomes, and no evidence of fixed inversions between species in the dunni group ( Heed 1962 ; Cordeiro et al 2014 ), though we do find several inversions between the next closest whole genome available, D. innubila on Muller elements B, C and D ( D. nigrodunni shown in Supplementary Figure 4B). We annotated the dunni group genomes using a transcriptome from D. innubila in MAKER ( Holt and Yandell 2011 ) and found between 10752 and 11581 genes in the assembled genomes of each species, most of which show orthology to previously identified genes in D. virilis, D. melanogaster or D. innubila (Supplementary Table 5) ( Hill et al 2019 ).…”
Section: Resultssupporting
confidence: 91%
“…D. nigrodunni x D. arawakhana ), whereas no crosses produced only males or only fertile males. Despite divergence on levels comparable to the D. melanogaster subgroup (Supplementary Figure 1 and Supplementary Table 3), there are no characterized inversions between species ( Stalker and Streisinger 1953 ; Cordeiro et al 2014 ), allowing differences across the species group to be investigated with a higher resolution than the D. melanogaster group allows. Given the variety in levels of divergence and isolation between species ( Figure 1 , Supplementary Figure 1), we next examined the patterns of divergence between species.…”
Section: Resultsmentioning
confidence: 99%
“…We considered the possibility that this species may no longer have a free dot chromosome, which would invalidate this comparison. However, while D. similis differs by two chromosome fusion events from D. cardini, its closest relative in our sample, neither fusion involved the F element (Cordeiro et al 2014).…”
Section: Resultscontrasting
confidence: 65%
“…The phylogeny of these species with divergence times was built using the TimeTree database on 7/29/2019 (Kumar et al 2017); all species were present in their database except for D. similis. As this species is a member of the dunni subgroup (Cordeiro et al 2014 Ovary Preps: Bottles of each stock were cleared of adults, and newly-eclosed adults were collected 6 hours later. To dissect females of each species at similar time points in development, when many oocytes would be in Prometaphase, we dissected females shortly before they began laying fertilized eggs.…”
Section: Methodsmentioning
confidence: 99%
“…In keeping with Haldane's rule (19), some produce sterile males, or no males at all (Figure 1, Figure 1, Supplementary Table 3), there are no characterized inversions between species (36,43), allowing differences across the species group to be investigated with a higher resolution than the D. melanogaster group allows.…”
Section: Resultsmentioning
confidence: 65%